2022
DOI: 10.5755/j01.itc.51.3.31510
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Forgery Face Detection Using Fuzzy Fisher Capsule Dual Graph

Abstract: In digital manipulation, creating fake images/videos or swapping face images/videos with another person is done by using a deep learning algorithm is termed deep fake. Fake pornography is a harmful one because of the inclusion of fake content in the hoaxes, fake news, and fraud things in the financial. The Deep Learning technique is an effective tool in the detection of deep fake images or videos. With the advancement of Generative adversarial networks (GAN) in the deep learning techniques, deep fake has becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This improvement was significant compared to similar models in other literature. For instance, Arunkumar P M's research team's fuzzy Fisher face model detection method achieved an accuracy of 89.32% in the dataset [12]. Styawati S's research team achieved the highest accuracy of 89% in sentiment classification using an SVM-based model [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This improvement was significant compared to similar models in other literature. For instance, Arunkumar P M's research team's fuzzy Fisher face model detection method achieved an accuracy of 89.32% in the dataset [12]. Styawati S's research team achieved the highest accuracy of 89% in sentiment classification using an SVM-based model [13].…”
Section: Discussionmentioning
confidence: 99%
“…To design an effective method that can accurately detect in-depth forged images or videos, the research team of Arunkumar P M proposed to utilize deep learning techniques and introduced a fuzzy Fisher face model with capsule biplots to detect different types of fake images or videos. The results showed that the method achieved 89.32% accuracy in the dataset [12].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The study considered only the faces of healthy people; however, it is known that some diseases such as facial palsy can significantly distort the characteristics of the face [95] while distorting its symmetry features [96], which can negatively affect biometric recognition using face. Additionally, the study did not consider adversarial attacks or attempts at face forgery with the aim of concealing identity or performing impersonation, which can decrease the performance of face recognition [97], Finally, the study did not address the fact that the use of masks to conceal faces may be done for legitimate reasons and not only by criminals. Therefore, the study did not consider the impact of increasing facial recognition accuracy in individuals who wear masks for safety or medical reasons.…”
Section: Limitationsmentioning
confidence: 99%